Efficiency of Special Autonomy of Papua: Does it Have an Effect on the Poverty Rate? - Kumala, Sepviana Nur; Mulyanto, Mulyanto; Sarjiyanto, Sarjiyanto (Puslatbang KDOD Lembaga Administrasi Negara, 2024)
Papua Province has received special autonomy funds since 2001. The provision of special autonomy funds is to help improve the development and welfare of the Papuan people. In this research, the level of welfare is measured by poverty. The efficiency of special autonomy needs to be considered so that budget allocation can be right on target. This research aims to analyse the efficiency of special autonomy in Papua and its influence on poverty levels in 2018 - 2022. Data Envelopment Analysis (DEA) and Panel Data Regression Analysis are the research methods used. The variables used in this research are education function expenditure, health function expenditure, public service expenditure, average length of schooling, life expectancy, percentage of households with adequate drinking water, and efficiency value with DEA. The research results show that several districts/cities in Papua have reached the efficiency level. Furthermore, the variables of efficiency level, adequate drinking water, life expectancy, and spending on education have a negative and significant effect on the poverty level in Papua. Meanwhile, the variables average length of schooling, expenditure on health functions, and expenditure on service functions do not affect the poverty level in Papua Province. The findings in this research could help the government and researchers know the efficiency of special autonomy. Furthermore, this study will show which factors help decrease the poverty rate in Papua Province